The Use of Public Language in Strategy: A Multidisciplinary Review and Research Agenda. (January 2016) - Gao, He; Yu, Tieying; Cannella, Albert A.
We review the literature on public language used as a strategic tool to engage stakeholders and competitors. We define public language as words and text issued by an organization with specific strategic intent. Our review classifies studies into four typical settings for the strategic use of public language: entrepreneurial, image threatening, financial, and competitive. Our review highlights the disparate theoretical backdrops across the four settings coupled with very limited prior attempts to integrate across these settings. We propose an integrated model that synthesizes the antecedents, consequences, and contingencies of the strategic use of public language and highlight several knowledge gaps. We end with a discussion of promising directions for future research.